2015
DOI: 10.1111/epi.13224
|View full text |Cite
|
Sign up to set email alerts
|

A noninterventional study evaluating the effectiveness and safety of lacosamide added to monotherapy in patients with epilepsy with partial‐onset seizures in daily clinical practice: The VITOBA study

Abstract: SummaryObjectiveEvidence for the efficacy and safety of adjunctive lacosamide in the treatment of partial‐onset seizures (POS) was gained during placebo‐controlled clinical trials in patients with treatment‐resistant seizures who were taking one to three concomitant antiepileptic drugs (AEDs). The VITOBA study (NCT01098162) evaluated the effectiveness and tolerability of adjunctive lacosamide added to one baseline AED in real‐world clinical practice.MethodsWe conducted a 6‐month observational study at 112 site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
31
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 17 publications
12
31
1
8
Order By: Relevance
“…1,26 For example, in the phase III monotherapy trial conducted in patients with newly diagnosed epilepsy, the most frequently reported ESL-related AEs (≥5% of patients) were dizziness, headache, somnolence, and fatigue, and the AEs that most frequently led to ESL discontinuation (≥1% of patients) were fatigue, nausea, dizziness, somnolence, and rash. [31][32][33] In a retrospective, non-interventional chart review of 439 patients with focal seizures, aged ≥16 years, who were treated with lacosamide monotherapy according to standard clinical practice in Italy, Spain, and the Netherlands, 6-month seizure freedom rates were 66.3% in patients treated with lacosamide as initial monotherapy and 63.0% 26 Therefore, it is perhaps unsurprising that the incidence of AEs leading to discontinuation was higher when ESL was used as adjunctive therapy versus monotherapy, since sodium channel blocking is the most common mechanism of have reported outcomes for the use of monotherapy with another member of the dibenzazepine family of AEDs, oxcarbazepine, in the clinical practice setting.…”
Section: Discussionmentioning
confidence: 99%
“…1,26 For example, in the phase III monotherapy trial conducted in patients with newly diagnosed epilepsy, the most frequently reported ESL-related AEs (≥5% of patients) were dizziness, headache, somnolence, and fatigue, and the AEs that most frequently led to ESL discontinuation (≥1% of patients) were fatigue, nausea, dizziness, somnolence, and rash. [31][32][33] In a retrospective, non-interventional chart review of 439 patients with focal seizures, aged ≥16 years, who were treated with lacosamide monotherapy according to standard clinical practice in Italy, Spain, and the Netherlands, 6-month seizure freedom rates were 66.3% in patients treated with lacosamide as initial monotherapy and 63.0% 26 Therefore, it is perhaps unsurprising that the incidence of AEs leading to discontinuation was higher when ESL was used as adjunctive therapy versus monotherapy, since sodium channel blocking is the most common mechanism of have reported outcomes for the use of monotherapy with another member of the dibenzazepine family of AEDs, oxcarbazepine, in the clinical practice setting.…”
Section: Discussionmentioning
confidence: 99%
“…Runge [11] evaluated the effectiveness of lacosamide for almost 6 months since its addition to therapy. Hussain [12] evaluated the effectiveness of cannabidiol (CBD) as an add-on therapy for patients with infantile spasms (IS) or Lennox–Gastaut (G) syndrome at ∼6.8 months after medication started.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LCM may work better as first add-on than later adjunctive treatment for uncontrolled POS 39,40. Several recent experiences suggest that LCM monotherapy, either as first-line or after conversion, may be a valuable option, even in the long term, for patients with focal epilepsy 4143.…”
Section: Emerging Treatment Options For Partial-onset Seizures (Poss)mentioning
confidence: 99%